Fe–Ni metal–organic frameworks with prominent peroxidase-like activity for the colorimetric detection of Sn2+ ions. Issue 19 (29th July 2020) - Hu, Ye; Yue, Chaochao; Wang, Jing; Zhang, Yuhua; Fang, Wenhui; Dang, Jiaqi; Wu, Ying; Zhao, Hong; Li, Zengxi
Abstract : The synthesized Fe–Ni-MOF could oxidize TMB to produce oxTMB with blue color. The presence of Sn 2+ ions could make the oxTMB color lighter, hence colorimetric detection of Sn 2+ ions is realized. Abstract : Fe–Ni-MOFs with different amounts of Fe are synthesized through a two-step template etching method. Kinetic analysis indicates that Fe–Ni-MOF exhibits prominent intrinsic peroxidase-like activity, which could catalytically oxidize 3, 3′, 5, 5′-tetramethylbenzidine (TMB) to produce oxidized TMB (oxTMB) with a blue color. As a peroxidase-mimicking MOF, Fe–Ni-MOF with its efficient stable catalysis properties is demonstrated to allow a sensitive colorimetric assay for Sn 2+ ions. The mechanism is explored, whereby Sn 2+ ions could reduce the peroxidase-like activity of Fe–Ni-MOF based on a redox interaction, making the oxTMB color lighter and decreasing the absorbance intensity at 652 nm. The linear determination of the Sn 2+ ion concentration using a UV-vis spectrometer ranges from 0.01 mM to 1.0 mM and from 1.0 mM to 4.0 mM. The presented Fe–Ni-MOF-based assay of Sn 2+ ions was successfully applied to real water samples.